Multiple Temporal‐Scale Photocarrier Dynamics Induced by Synergistic Effects of Fluorination and Chlorination in Highly Efficient Nonfullerene Organic Solar Cells. Issue 4 (30th January 2020) - Zhang, Kang-Ning; Niu, Meng-Si; Jiang, Zhi-Nan; Chen, Zhi-Hao; Wang, Tong; Wei, Meng-Meng; Qin, Chao-Chao; Feng, Lin; Qin, Wei; So, Shu-Kong; Hao, Xiao-Tao
Abstract : Fluorination and chlorination have yielded a novel class of materials and achieved tremendous progress in enhancing photovoltaic efficiency in organic solar cells (OSCs). However, their effects on photocarrier dynamics remain elusive in these organic photovoltaic systems. Herein, a comprehensive study on the underlying mechanisms is conducted based on a 2 × 2 photovoltaic matrix, consisting of PBDB‐T, PBDB‐T‐2Cl, ITIC, and IT4F. Chlorination of donors enhances exciton migration and relaxation rates and promotes the extraction of polarons. The more efficient charge transfer and a larger proportion of long‐lived polarons are observed in fluorine‐containing acceptor‐based systems, which are in favor of charge generation in the actual devices. According to the enlarged dielectric constant in the PBDB‐T‐2Cl:IT4F blend, the improved exciton delocalization, the decreased exciton binding energy, and Coulomb capture radius are obtained relative to other three binary systems, which can increase charge separation efficiency and reduce the probability of bimolecular recombination. The simultaneous fluorination and chlorination can optimize molecular packing and nanoscale phase separation, facilitating effective exciton diffusion, exciton dissociation, and charge transport. These results highlight the important role of fluorination and chlorination on these fundamental mechanisms, possibly resulting in some new molecular design principles toward high‐performance OSCs. Abstract : The influence of the synergetic effects of fluorination and chlorination on multiple temporal‐scale photocarrier dynamics is thoroughly studied based on a 2 × 2 matrix of organic solar cells consisting of PBDB‐T, PBDB‐T‐2Cl, ITIC, and IT4F. Both fluorination and chlorination play a positive role in exciton diffusion, exciton dissociation, charge transport, and collection, contributing to the improvement of photovoltaic performance.